Analysis and critique of 'Transforming children and young people's mental health provision: A green paper': Some implications for refugee children and young people. (September 2020) - Cox, Pat; McDonald, Jane March
Adopting a children's rights perspective, a critique and analysis underpinned by documentary research methodology was undertaken in order to assess the extent to which the government's Green Paper (Department of Health and Social Care and Department of Education, 2017. Transforming children and young people's mental health provision: a green paper. Available at:https://www.gov.uk/government/consultations/transforming-children-and-young-peoples-mental-health-provision-a-green-paper (accessed 7 December 2017)) addresses the mental health and well-being needs of refugee children and young people in England and Wales, identifying strengths, limitations and challenges for future policy and practice. Findings suggest that there is much of potential benefit to refugee children and young people's future mental health and well-being. However, a paradigm shift, explicit in implications, scale and time frame, will be required, if the Green Paper is to achieve those changes in attitudes, practice and service delivery which it anticipates. We argue that this Green Paper's overarching challenge is that it is premised on Western-centric models in its understanding of the experiences of refugee children and young people, and management of trauma and mental health. It fails to recognize the meanings and significance of culture, and of diversity and difference, and the need to invest in all communities in facilitating engagement and support for children and young people's mental health issues.